125. eGISP: Enhanced Surveillance of Neisseria gonorrhoeae Antimicrobial Susceptibility in the United States. (26th November 2018) - Quilter, Laura; Cyr, Sancta St; Abitria, Vincent; Ancharski, Andrew; Bautista, Ilene; Bazan, Jose; Carifo, Karen; Ervin, Melissa; Harrison, Rebecca; Hoogenboom, Aaron; Peterson, Amy; Pham, Cau; et al.
Abstract: Background: The Gonococcal Isolate Surveillance Project (GISP), which monitors trends in N. gonorrhoeae susceptibility among men with gonococcal urethritis in sexually transmitted disease (STD) clinics, has informed treatment recommendations for 3 decades. However, it has been speculated that susceptibility patterns may differ in women, as well as in the pharynx and rectum. We describe preliminary findings from the enhanced GISP (eGISP), which expands surveillance to pharyngeal, rectal, and endocervical isolates. Methods: In August 2017, select jurisdictions were funded to collect urogenital and extragenital specimens from men and women seen in participating STD clinics. Positive gonorrhea cultures were sent to regional laboratories for antimicrobial susceptibility testing (AST) by agar dilution. Isolates with elevated minimum inhibitory concentration (MIC) to azithromycin (AZI) (MIC ≥2.0 μg/mL), cefixime (CFX) (MIC ≥0.25 μg/mL), and/or ceftriaxone (CRO) (MIC ≥0.125 μg/mL) were designated as Alert isolates. Clinical and epidemiological data were linked to AST results. Results: From August 2017 to February 2018, 4 clinics in 4 jurisdictions submitted 468 positive gonococcal specimens for AST; 36.1% were from men who have sex with men (MSM), 51.9% from men who have sex with women (MSW), and 12.0% from women. Overall, 71.8% were urethral, 7.9% endocervical, 7.1% rectal, and 13.2% pharyngeal. Seventy-two isolates (15.4%) were Alerts: 97.2% ( N = 70) had elevated MICs to AZI, 2.8% ( N = 2) had elevated MICs to CFX, and none had elevated MICs to CRO. No isolate had elevated MICs to both AZI and CFX. Among MSM, 15.9% of urogenital isolates and 16.1% of extragenital isolates had an elevated AZI MIC. Among MSW, 11.8% of urogenital isolates and 14.3% of pharyngeal isolates had an elevated AZI MIC. Among women, 24.3% of endocervical isolates and 26.3% of extragenital isolates had an elevated AZI MIC. Conclusion: Preliminary eGISP data suggest that enhanced surveillance of pharyngeal, rectal, and endocervical isolates is feasible and that elevated MICs to azithromycin are common among males and females. Including isolates from extragenital anatomic sites and women may help strengthen N. gonorrhoeae surveillance capacity. Disclosures: All authors: No reported disclosures.